Determinants of agricultural labor productivity of small farmers its implications to agricultural education - Dechavez, Marcelino Andora 1937- (1985)
The investigation sought to determine the effects of human capital and psychological and socioeconomic predictors on small farmers' earnings in terms of average agricultural labor productivity per person per hectare per month (AALPPHM). Multistage random sampling procedure was employed in drawing to an interview 732 small farmer respondents from Western Visayas who were household heads, had been farming for at least four consecutive years in farms below 25 hectares and were not farm managers. Multiple regression and path analysis identified the following predictors: (1) natural log of total farming experience, (2) meal quality, (3) adaptability, (4) school typology, (5) acess to technology, (6) presence of irrigation, and (8) civil status.
Thesis (Ed.D.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Human capital; Agricultural laborers; Labor productivity -- Economic aspects; Labor productivity -- Psychological aspects; Labor productivity -- Social aspects